+0  
 
+1
361
2
avatar

n^2(n+1)^2/4+4(n+1)^3/4

Guest Apr 26, 2017
 #1
avatar+90056 
+1

 

n^2(n+1)^2/4+4(n+1)^3/4  =

 

[ (n + 1)^2 [ n^2  + 4(n + 1) ] / 4

 

[ (n + 1)^2 [ n^2   + 4 n  + 4] / 4  =

 

[ (n + 1)^2  [  n + 2] ^2  / 4

 

 

 

cool cool cool

CPhill  Apr 26, 2017
 #2
avatar+54 
+1

n2(n + 1)2 / 4 + 4(n + 1)3 / 4

n2(n + 1)2 / 4 = n2(n2 + 2n + 1) / 4 = (n4 + 2n3 + n2) / 4

4(n + 1)3 / 4= n3 + 3n2 + 3n + 1

n4 + 2n3 + n2 + 4n3 + 12n2 + 12n + 4 = (n4 + 6n3 + 13n2 + 12n + 4) / 4

Doboman  Apr 27, 2017

32 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.